THE INFLUENCE OF AUTOCRATIC LEADERSHIP AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF THE “ABC” CITY CULTURE AND TOURISM OFFICE - Siti Maesaroh Solihah; Andi Budiawan; Nugi Mohammad Nugraha (Universitas La Tansa Mashiro, 2021)
The purpose of this study was to determine the magnitude of the influence of autocratic leadership and work discipline on employee performance at the “ABC” City Tourism and Culture Office, either simultaneously or partially. In this research, the object to be studied is the “ABC” City Culture and Tourism Office. The scope of the study was to determine the extent of the influence of autocratic leadership and work discipline on the performance of employees at the “ABC” City Culture and Tourism Office, with a sample of 76 respondents. The results of the partial analysis of the relationship between autocratic leadership and performance are tcount 2.149 > 1.993 (ttable), so it can be concluded that autocratic leadership (X1) has a partial effect on performance (Y). The results of the partial analysis of the relationship between work discipline and performance are tcount 10.049 > 1.993 (ttable), so it can be concluded that work discipline (X2) has a partial effect on performance (Y). The results of the simultaneous analysis are Fcount 51.794 > 3.12 (Ftable), so it can be concluded that there is an influence between autocratic leadership (X1) and work discipline (X2) simultaneously on performance (Y).